Cytotoxicity Induction in A549 Alveolar Epithelial Cells by Mycobacterium tuberculosis Isolates Cultured in the Presence and Absence of Oxygen - Olubisi T. Ashiru ,; A. Willem Sturm, (Journal of Basic & Applied Sciences, 2015)
Background: The emergence of drug resistant Mycobacterium tuberculosis and studies on clinical isolates of drug resistant M. tuberculosis highlight the need to obtain additional valuable information on this organism. In this study, we report on M. tuberculosis clinical isolates and laboratory strain induced cytotoxicity in A549 alveolar epithelial cells in vitro. A549 cells were infected with 15 clinical isolates (members of the Beijing and F15/LAM4/KZN families, as well as isolates with unique DNA fingerprint), and two laboratory strains of M. tuberculosis grown in the presence of oxygen, and absence of oxygen. Lactate dehydrogenase released from A549 cells was quantified after infection to evaluate necrosis. Results:The isolates grown in the absence of oxygen had a higher level of cytotoxicity than those grown in the presence of oxygen. Cytotoxicity levels induced by F15/LAM4/KZN and Beijing isolates grown in the absence of oxygen ranged from 18.4%-35.7% and 17.7%-27.5% respectively. The highest cytotoxicity level (35.7%) was produced by an extensively drug resistant isolate that belonged to the F15/LAM4/KZN family. Growth in the presence of oxygen resulted in lower levels of cytotoxicity, ranging from 14.3%-22.4% by the F15/LAM4/KZN isolates, and 13%-23.3% by the Beijing isolates. Isolates with unique DNA fingerprint induced cytotoxicity levels between 3.5%-8.5% (oxygen) and 5.3%-10.7% (no oxygen). The H37Rv and H37Ra bacilli induced cytotoxicity levels of 3.9% and 2.9% (oxygen) respectively and 5.7% and 3.3% (no oxygen) respectively. Conclusion:These results correlate well with our previous findings on the adhesion and invasion rates of these isolates. The increased tissue destruction induced by the F15/LAM4/KZN isolate compared to the other isolates attest to its virulence and may partly explain the high mortality rates of patients infected with this strain in Kwa Zulu-Natal in 2005.